Identification of the nettle caterpillar in smallholding oil palm plantation cultivated on peatland in Ogan Ilir, South Sumatra, Indonesia - ERISE ANGGRAINI; TIYAS SETIAWATI; SITI HERLINDA; CHANDRA IRSAN; MULAWARMAN MULAWARMAN; NUNI GOFAR; A. MUSLIM; WEI HONG LAU (Society for Indonesian Biodiversity, 2025)
Abstract. Anggraini E, Setiawati T, Herlinda S, Irsan C, Mulawarman, Gofar N, Muslim A, Lau WH. 2025. Identification of the nettle caterpillar in smallholding oil palm plantation cultivated on peatland in Ogan Ilir, South Sumatra, Indonesia. Biodiversitas 26: 36-44. Nettle caterpillars are a major pest in oil palm plantations, posing a significant threat to the productivity and sustainability of this crop. These voracious leaf-feeding caterpillars can cause severe damage, hindering plant growth, reducing fruit production, and even leading to the mortality of oil palm trees. This study aimed to identify the species of caterpillars that inflict damage, their physical traits, population densities, and the symptoms of their attacks. This study employed direct observation and documentation of caterpillar species in the field. Observations were conducted to assess the extent of damage inflicted by caterpillars in the field. Subsequently, document using a camera, collect field samples, and identification of the nettle caterpillars found in oil palm plantation cultivated on peatland in Ogan Ilir, South Sumatera, Indonesia. This investigation identified three species of caterpillars: Setora nitens, Birthosea bisura, and Parasa lepida. These three species of caterpillars typically exhibit similar coloration but possess distinct morphological traits. The S. nitens species predominates among the largest number of species. Caterpillars consume both young and mature oil palm leaves, remaining only in the midrib. Additional indications of the attack include perforations in the leaves. The incidence of caterpillar assaults may attain 100% of nettle caterpillar infestation, accompanied by an attack rate of 57.75%. This study concludes that three primary species of nettle caterpillar were identified in oil palm plantations, exhibiting indications of damage classified as fairly severe. Thus, effective management of nettle caterpillars is crucial to maintaining the productivity and profitability of oil palm plantations.